(untitled) (Altre Modernità, 2018)
Graham Swift, Mothering Sunday. A Romance (London, Scribner, 2016, 149 pp. ISBN 9781471155246) Graham Swift, Un giorno di festa. Una storia d’amore. (Vicenza, Neri Pozza, 2016, 144 pp. ISBN 9788854513891) di Ilaria Villa